Relationship Between Personality Traits and Self-Differentiation with Psychological Hardiness in Students - Aghajan, Mahya (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the relationship between personality traits and self-differentiation with psychological hardiness among university students.Methods and Materials: This study employed a descriptive correlational design. The statistical population consisted of university students in Tehran, from whom 384 participants were selected using multistage cluster sampling based on the Morgan sampling table. Data were collected using the NEO Personality Inventory developed by Costa and McCrae, the Psychological Hardiness Questionnaire developed by Suzanne Kobasa, and the Differentiation of Self Inventory developed by Drake. The reliability of the instruments was confirmed using Cronbach’s alpha coefficients. Data were analyzed using descriptive statistics, Pearson correlation coefficients, and simultaneous multiple regression analysis.Findings: The findings indicated that neuroticism had a significant negative relationship with psychological hardiness (r = -.61, p < .01) and self-differentiation (r = -.52, p < .01). In contrast, extraversion, openness to experience, agreeableness, and conscientiousness demonstrated significant positive correlations with psychological hardiness and self-differentiation. Multiple regression analysis revealed that extraversion (β = .35), agreeableness (β = .18), and conscientiousness (β = .18) significantly predicted psychological hardiness, whereas neuroticism and openness to experience were not significant predictors. The regression model explained 52% of the variance in psychological hardiness. Furthermore, neuroticism (β = -.34), extraversion (β = .52), and conscientiousness (β = -.34) significantly predicted self-differentiation, while openness to experience and agreeableness did not significantly contribute to the prediction model. Personality traits explained 42% of the variance in self-differentiation.Conclusion: The findings demonstrated that personality traits play a significant role in predicting psychological hardiness and self-differentiation among university students. Extraversion, agreeableness, and conscientiousness were associated with greater psychological resilience and emotional adjustment, whereas neuroticism was associated with lower levels of hardiness and differentiation.